Borrelia burgdorferi protein interactions critical for microbial persistence in mammals. (8th July 2018) - Bernard, Quentin; Thakur, Meghna; Smith, Alexis A.; Kitsou, Chrysoula; Yang, Xiuli; Pal, Utpal
Abstract: Borrelia burgdorferi is the causative agent of Lyme disease that persists in a complex enzootic life cycle, involving Ixodes ticks and vertebrate hosts. The microbe invades ticks and vertebrate hosts in spite of active immune surveillance and potent microbicidal responses, and establishes long‐term infection utilising mechanisms that are yet to be unravelled. The pathogen can cause multi‐system disorders when transmitted to susceptible mammalian hosts, including in humans. In the past decades, several studies identified a limited number of B. burgdorferi gene‐products critical for pathogen persistence, transmission between the vectors and the host, and host–pathogen interactions. This review will focus on the interactions between B. burgdorferi proteins, as well as between microbial proteins and host components, protein and non‐protein components, highlighting their roles in pathogen persistence in the mammalian host. A better understanding of the contributions of protein interactions in the microbial virulence and persistence of B. burgdorferi would support development of novel therapeutics against the infection.